Study of Pasture Productivity for Semi-Intensive Cattle System during Dry Season in the South Konawe Regency, Southeast Sulawesi - Ahmat Endang Two Sulfiar; Bayu Andri Atmoko; Budi Guntoro; I Gede Suparta Budisatria (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This study was aimed to evaluate the characteristics and productivity of pasture for semi-intensive cattle system in South Konawe Regency during dry season. The study was conducted in August-September 2019 as dry season based on the weather condition and was determine by Department of Statistics Center of South Konawe Regency. A total of 55 selected smallholder farmers in two areas in South Konawe Regency, namely West Ranomento (30) and Konda (25) Districts. Data were obtained by interview to find out the farmers profile and pasture characteristics. Production was measured by forage sampling (1x1m) to calculate annual production. Samples were proximately analyzed to calculate dry matter production and the carrying capacity. Data were analyzed descriptively and statistically with an independent sample t-test. The botanical composition in both locations was highly dominated (>90%) by field grasses. The grassland ownership was not different between two areas. Grassland ownership at West Ranomento and Konda were 0.78±0.14 and 0.21±0.04 Ha/farmer, respectively. The pasture production between West Ranomento (2.27±0.10 ton/ha) and Konda District (1.76±0.05 ton/ha) was significantly different (p<0.05),. Pasture production and carrying capacity indicated that conditions in West Ranomento were significantly higher (p<0.05) compared to Konda District. The fresh forages production was 10.98±2.26 vs. 2.17±0.51 ton/year, forages that can be consumed was 3.30±0.67 vs. 3.30±0.67ton/year, dry matter production was 0.72±0.15 vs. 0.18±0.04 ton/year and carrying capacity was 0.22±0.04 vs. 0.05±0.01 AU/year respectively. It was concluded that the pasture productivity at the study area during dry season was very low based on productivity and carrying capacity.